Flexible and Transparent Organic Phototransistors on Biodegradable Cellulose Nanofibrillated Fiber Substrates. Issue 9 (26th February 2018) - Park, Junsu; Seo, Jung‐Hun; Yeom, Seung‐Won; Yao, Chunhua; Yang, Vina W.; Cai, Zhiyong; Jhon, Young Min; Ju, Byeong‐Kwon
Abstract: This work demonstrates flexible, transparent phototransistors that can detect visible light with nontoxic organic active materials on biodegradable substrates toward environment‐friendly electronics. The molybdenum trioxide (MoO3 )‐buffered indium zinc oxide as high‐performance hole injector and transparent electrodes is applied for the first time to organic phototransistors on cellulose nanofibrillated fiber substrates to achieve more than 70% of transmittance in the visible range (400–750 nm) while showing high conductivity under multiple bendings. Excellent electrical switching characteristics are obtained from transistors using a pentacene active layer with a saturation mobility value of 1.40 cm 2 V −1 s −1 . The phototransistors, which can detect visible light and perform in two operation modes, exhibit a maximum responsivity of 54.8 A W −1 and a photosensitivity of 24.4 under white light illumination at an intensity of 0.12 mW cm −2 . Moreover, the devices show a stable operation during mechanical bending tests with radii ranging from 100 to 5 mm and cyclic bending tests of up to 2000 cycles at a fixed radius of 5 mm. The results suggest that these flexible phototransistors with properties of transparency and biodegradability have considerable potential for use in low‐cost and eco‐friendly disposable sensor systems. Abstract : Flexible and transparent organic phototransistors on biodegradable substrates are demonstrated toward environment‐friendly electronics. The combination of non‐toxic pentacene active material and biodegradable substrate allows eco‐friendly electronics and the molybdenum trioxide‐buffered indium zinc oxide electrodes enable the high transparency in the visible range. The comprehensive characteristics offer great promise for use in eco‐friendly disposable sensors toward future medical and environment monitor applications.